ANALYSIS OF THE INTRINSIC ELEMENTS OF THE NOVEL DANGEROUS NERD BY SISKA FEBRIANTI - Maria Magdalena Fitri (Prawara: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This Dangerous Nerd novel is the work of siska pebrianty, where this novel tells about a child whose parents have been killed by someone who has to solve his problem, this novel is full of mystery and puzzles therefore this girl came to town to avenge his parents and eradicate the chain of murders that occurred in the past. This type of research is qualitative using the data source, namely the Dangerous Nerd novel. The data collection technique is using literature study and the analysis technique is using descriptive method. The results of this study are showing themes, plots, characters and characterizations, point of view, language style and message. The purpose of this research is to make this novel known among the wider community and to become a source of new knowledge for the community.